Burden of microbial pathogens–associated infectious diseases in Asian older adults: a systematic analysis derived from the global burden of disease 2021 - Chen, Lin; Lou, Yuhang; Yang, Jie; Zhang, Kai; Liu, Xiaoli; Fan, Yushi; Zhang, Xinyun; Wang, Qing; Yang, Qianqian; Chen, Qitao; Wang, Meihua; Li, Ya; et al. (Frontiers in Public Health, 2025)
BackgroundMicrobial pathogens–associated infectious diseases significantly threaten older adults, especially in Asia, home to over 60% of the world’s older adults. Age-related immune decline increases infection-related mortality and disability. Using Global Burden of Disease (GBD) 2021 data, we quantify the burden attributable to 34 microbial pathogens in older adults across Asia.MethodWe conducted a cross-sectional analysis of GBD 2021 data to estimate deaths and disability-adjusted life-years (DALYs) attributable to microbial pathogens in individuals aged ≥ 60 years across the Asia continent and 46 of its countries. Microbial pathogens attribution followed the GBD 2021 framework (34 microbial pathogens). Age-standardized death and DALYs rates were calculated, regional variations analyzed using socio-demographic index (SDI), and uncertainty intervals (UIs) estimated via Monte Carlo simulations.FindingsIn 2021, Streptococcus pneumoniae (S. pneumoniae) was the leading cause of infectious disease burden among the older adults, with 175,929 deaths (95% UI: 151,002–197,658) and 2,799,883 DALYs (95% UI: 2,430,432–3,129,747), followed by Staphylococcus aureus (S. aureus). By contrast, lower-burden aetiologies included Listeria monocytogenes, Enteropathogenic Escherichia coli, and Aeromonas. The burden varied across regions, with Cambodia having the highest age-standardized DALYs rate (18,186.08 per 100,000), while high-SDI countries like Qatar had lower mortality. S. pneumoniae peaked at ages 80–84 years, disproportionately affecting males (17,312 death; 95% UI: 15,215–19,318) compared to females (15,545 death; 95% UI: 12,191–18,471). A strong inverse correlation was observed between SDI and pathogens burden (p < 0.01).InterpretationAmong Asian adults aged ≥ 60 years, the 2021 microbial pathogens–attributable burden was led by S. pneumoniae, followed by S. aureus. The SDI inverse gradient was strongest for diarrhoeal disease and meningitis, and weaker for lower respiratory infections. Subregional heterogeneity persisted after age-standardization, implying drivers beyond SDI. These findings support prioritizing adult pneumococcal vaccination programs, strengthening hospital infection-prevention and control with a focus on staphylococcal and Klebsiella transmission through antimicrobial stewardship and hand hygiene, and investing in water, sanitation, and hygiene (WASH) infrastructure particularly in community and healthcare settings. Addressing these disparities requires tailored national strategies that align with local pathogens prevalence, health system capacity, and SDI context.